1977
DOI: 10.3109/00365527709180942
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Mucosal Adrenergic Innervation and Enterochromaffin Cells in Ulcerative Colitis and Irritable Colon

Abstract: Rectal mucosal biopsies of 13 patients suffering from ulcerative colitis, 7 patients presenting symptomatology typical of irritable colon, and 7 control persons were studied by the recently introduced glyoxylic-acid-induced fluorescence histochemical method. In ulcerative colitis, compared to control specimens: 1) the density of the adrenergic nerve network was significantly pronounced; 2) the mean diameter of the varicosities and the proportional share of large varicosities were increased, as well as the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 7 publications
4
52
0
Order By: Relevance
“…Increased 5-HT secretion (2,17) and decreased levels of 5-HT transporters (SERT) (8) have been noted in IBD, the latter, a reuptake mechanism facilitating degradation of 5-HT. In diarrhea-dominated IBS (D-IBS), the EC cell number is also increased (31), which is accompanied by elevated postprandial plasma 5-HT (1). In addition, SERT is downregulated in D-IBS (8).…”
mentioning
confidence: 97%
“…Increased 5-HT secretion (2,17) and decreased levels of 5-HT transporters (SERT) (8) have been noted in IBD, the latter, a reuptake mechanism facilitating degradation of 5-HT. In diarrhea-dominated IBS (D-IBS), the EC cell number is also increased (31), which is accompanied by elevated postprandial plasma 5-HT (1). In addition, SERT is downregulated in D-IBS (8).…”
mentioning
confidence: 97%
“…Although 5-HT has been known to play a major role in regulating a number of physiological functions in the GI tract, elevated levels of serotonin have been implicated in the pathophysiology of disease states such as carcinoid syndrome (7), celiac disease (28), irritable colon (29), and dumping syndrome (30). Previous studies have shown that 5-HT administration in vivo induces Cl Ϫ secretion in the rabbit small intestine (31) and acts as a mediator of diarrhea in patients with carcinoid syndrome associated with a net secretion of water and electrolytes (32).…”
Section: -Htmentioning
confidence: 99%
“…IBS is considered to be stress-related functional bowel disease, which is characterized by abdominal pain and altered bowel habit (12). The symptoms of IBS are correlated to I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I I altered bowel motility (9) and the number of enterochromaffin cells is increased in the rectal mucosa of IBS patients (10). These results suggest that 5-HT is involved in the pathogenesis of this disorder.…”
Section: Introductionmentioning
confidence: 99%